Effects of sintering temperature on the structural and electrochemical properties of SrFe0.5Ti0.5O3‐δ perovskite cathode. Issue 2 (6th November 2017) - Baharuddin, Nurul Akidah; Muchtar, Andanastuti; Somalu, Mahendra Rao; Anwar, Mustafa; Shaikh Abdul Kader Abdul Hameed, Muhammed Ali; Mah, Joelle
Abstract: The effects of sintering temperature on the structural and electrochemical properties of SrFe0.5 Ti0.5 O3‐δ perovskite cathode film was investigated. For the structural properties of SrFe0.5 Ti0.5 O3‐δ film sintered at a temperature ranging from 900‐1300°C, changes in surface and cross‐sectional microstructure were studied. Surface porosity and micro hardness were analyzed. The relationship of the structural properties with the electrical and electrochemical performances of the SrFe0.5 Ti0.5 O3‐δ film was examined. The high densification of the film sintered at 1300°C led to the better electrical conductivity of 16.38 S cm −1 than the 4.86 S cm −1 of the film sintered at 900°C at an operating temperature of 800°C. For the electrochemical performance, the SrFe0.5 Ti0.5 O3‐δ film sintered at 1300°C gained a low area specific resistance (ASR) value of 38.70 Ω cm 2 at 800°C. The ASR further decreased to 0.99 Ω cm 2 for the thicker film sintered at the same temperature.